Literature Review: Compliance With Five Moments Hand Hygiene In Healthcare Facilities In An Effort To Reduce Healthcare-Associated Infections - Aryana, I Gusti Ngurah; Agustini, Ni Luh Putu Inca Buntari; Adianta, I Ketut Alit; Sagitarini, Putu Noviana (Institute Teknologi dan Kesehatan (ITEKES) Bali, 2025)
Facilities susceptible to being infected with hospital germs known as healthcare-associated infections. World Health Organization through guidelines and strategies to improve five-moment hand hygiene includes improving infrastructure to provide hand medical means. The learning is targeted how a literature review of health workers' compliance to perform five model clean hands in medical facilities to minimize the incidence of infection related to health services. The method of study was literature review study design with An optimal strategy, for example, is searching for sources in various international journal data. The result was based on a literature review of 15 research journals, namely Google Scholar, Science Direct and Pubmed, it could be concluded that the compliance of health workers in performing five-moment hand hygiene varies greatly and the predictors that influence it are also very diverse. Five-moment clean hands optimal for reducing the incidence of healthcare-associated infections. Keywords: Nurse, hand hygiene, compliance